A Rational Approach to the Treatment of Acute Tonsillopharyngitis in Children - O.E. Chernyshova (Zaslavsky O.Yu., 2016)
In this paper, we consider a variant of the local anti-inflammatory therapy in acute tonsillopharyngitis in children with anti-inflammatory, analgesic effect, both as monotherapy and in combination with antibacterial agents.